2015
DOI: 10.1007/s10529-015-1949-3
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of human mesenchymal stem cell differentiation by combination treatment with 5-azacytidine and trichostatin A

Abstract: HMAs and HDACs enhanced in vitro differentiation of MSCs, which was maximized when the two drugs were combined, with HMA having the dominant effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 15 publications
1
10
0
Order By: Relevance
“…found that TSA enhanced hMSCs chondrogenesis in pellets cultured in chondrogenic media 46 . Kim et al found TSA treatment increased type II collagen expression over control levels seen during hMSC chondrogenesis 47 . The mechanism by which TSA affects cartilage development and degradation may be attributable to histone modification by HDACs.…”
Section: Discussionmentioning
confidence: 97%
“…found that TSA enhanced hMSCs chondrogenesis in pellets cultured in chondrogenic media 46 . Kim et al found TSA treatment increased type II collagen expression over control levels seen during hMSC chondrogenesis 47 . The mechanism by which TSA affects cartilage development and degradation may be attributable to histone modification by HDACs.…”
Section: Discussionmentioning
confidence: 97%
“…For example, chromatin modification by epigenetic drugs has been proven to enhance multilineage differentiation of MSCs to osteocytes, adipocytes chondrocytes, and cardiomyocytes [192021]; however, the data regarding the influence of AZA on MSCs remain controversial [22]. We have previously observed that a combination of AZA and trichostatin A treatment enhanced multilineage differentiation, with AZA-induced hypomethylation being the main contributing mechanism [13]. However, in the present study, we observed no significant changes in the expression levels of key regulatory molecules in 2D-MSCs following AZA treatment.…”
Section: Discussionmentioning
confidence: 99%
“…For adipogenesis, cells plated in 24-well plates and grown to confluence were incubated in adipogenic differentiation medium for 2 weeks (Thermo Fisher Scientific, Waltham, MA, USA), and were either used for RNA isolation for genetic analysis or stained with Oil Red O for marker detection (Sigma). For osteogenesis, cells grown on 24-well plates to confluence were incubated with osteogenic differentiation medium (DMEM with 10% MSC-FBS, 10 −7 M dexamethasone, 10 mM β-glycerophosphate, and 0.3 mM ascorbic acid) [13] for 2 weeks, and were either processed for RNA isolation or stained with alkaline phosphatase (ALP) to highlight calcium deposits.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous study, epigenetic modification of human MSCs (hMSCs) with HMAs plus HDACi resulted in higher expression of Runx-2, BDNF, and Sox-9 than the control treatment. HMAs and HDACi enhance the in-vitro differentiation of MSCs, suggesting that epigenetic modification could alter the function of hMSCs [ 22 ].…”
Section: Introductionmentioning
confidence: 99%